2021
DOI: 10.2169/internalmedicine.6652-20
|View full text |Cite
|
Sign up to set email alerts
|

Malpractice Claims of Internal Medicine Involving Diagnostic and System Errors in Japan

Abstract: Objectives Medical litigation resulting from diagnostic errors leads to lawsuits that are time-consuming, expensive, and psychologically burdensome. Few studies have focused on internists, who are more likely to make diagnostic errors than others, with assessments of litigation in terms of system and diagnostic errors. This study explored factors contributing to internists losing lawsuits and examined whether system or diagnostic errors were more important on the outcome. Methods Data regarding 419 lawsuits ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Other predictive factors for an accepted claim (medical doctors' loss) using LightGBM were diagnostic error, reason for litigation (diagnosis), facility size, and patient age. These results are consistent with those of previous studies on internal medicine and orthopedic surgery [5,8,12]. Various previous studies have estimated that physician diagnostic errors in the outpatient setting may range from 3-10%, and the negative impact of diagnostic errors is a significant and urgent problem that needs to be addressed [9,30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other predictive factors for an accepted claim (medical doctors' loss) using LightGBM were diagnostic error, reason for litigation (diagnosis), facility size, and patient age. These results are consistent with those of previous studies on internal medicine and orthopedic surgery [5,8,12]. Various previous studies have estimated that physician diagnostic errors in the outpatient setting may range from 3-10%, and the negative impact of diagnostic errors is a significant and urgent problem that needs to be addressed [9,30].…”
Section: Discussionsupporting
confidence: 91%
“…It is better for medical staff to understand the factors that influence litigation outcomes [3,4]. System and diagnostic errors have been reported as contributing factors to malpractice claims [5][6][7][8] and recently recognized as essential issues in medical economics, health care quality, and patient safety [9,10]. In addition, previous studies have indicated the following factors associated with litigation outcomes: night shift, unnecessary surgery, sequelae, and death [5,8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 In-depth evaluation of diagnostic errors from the viewpoint of the professional can improve quality of clinical care. 14 , 15 Numerous case reports on diagnostic errors as resources to improve the quality of diagnosis have been published in Japan, and research is being conducted on the epidemiology of diagnostic errors, 15 , 16 diagnostic error education, 17 clinical prediction rules, artificial intelligence (AI)-based diagnosis, 18 and diagnostic concepts. 19 Generalists working in various settings may discover research interests in the course of their daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the trajectory of evaluation prior to ordering the first diagnostic test can be influenced by cognitive biases, such as anchoring or premature closure [33]. Other analyses have further distinguished cognitive and system-related error among subcategories of diagnostic error [34,35]. Knowledge deficits, inadequate data gathering, and incomplete synthesis also contributed to cognitive error.…”
Section: Diagnostic Errormentioning
confidence: 99%